2008
DOI: 10.2217/17460875.3.3.273
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide signaling in cancer and stem cells

Abstract: Most of the previous work on the sphingolipid ceramide has been devoted to its function as an apoptosis inducer. Recent studies, however, have shown that in stem cells, ceramide has additional nonapoptotic functions. In this article, ceramide signaling will be reviewed in light of 'systems interface biology': as an interconnection of sphingolipid metabolism, membrane biophysics and cell signaling. The focus will be on the metabolic interconversion of ceramide and sphingomyelin or sphingosine-1-phosphate. Lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(84 citation statements)
references
References 366 publications
1
81
0
Order By: Relevance
“…(19), PDGF signaling (20,21), sphingosine-1-phosphate (S1P) signaling (22), and mTOR signaling (23)(24)(25)(26). In addition, we observed an inhibition of the tumor suppressor PTEN signaling (27)(28)(29) and ceramide signaling (30). In ts-101 KO cells, two pathways related to cell transformation and cancer development are overactivated, namely, S1P signaling (22) and glutamate receptor signaling (31).…”
Section: Resultsmentioning
confidence: 90%
“…(19), PDGF signaling (20,21), sphingosine-1-phosphate (S1P) signaling (22), and mTOR signaling (23)(24)(25)(26). In addition, we observed an inhibition of the tumor suppressor PTEN signaling (27)(28)(29) and ceramide signaling (30). In ts-101 KO cells, two pathways related to cell transformation and cancer development are overactivated, namely, S1P signaling (22) and glutamate receptor signaling (31).…”
Section: Resultsmentioning
confidence: 90%
“…S1P acts as second messenger intracellularly as well as a ligand for membrane-bound G-proteincoupled receptors, and it plays an important role in regulating central cellular processes, such as cell growth, cell apoptosiss, differentiation and motility (Köberle et al, 2010;Modra., 2006;Bieberich E, 2008;Reynolds CP., 2004) by up-regulating several antiapoptotic pathways including phosphatidy-linositol-kinase or NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…Ceramide mediates a wide array of stress signals such as anticancer treatments leading to apoptosis, whereas S1P exerts prosurvival capabilities by antagonizing ceramide effects (Modrak et al, 2006). So a ceramide/S1P rheostat has been hypothesized to determine the fate of cell, such that the relative cellular concentrations of ceramide and S1P determine whether a cell proliferates or undergoes apoptosis (Andrieu-Abadie and Levade, 2002;Reynolds et al, 2004;Bieberich et al, 2008). At the same time, previous work using Dictyostelium discoideum as a model for studying drug resistance showed that mutants lacking sphingosine-1-phosphate (S1P) lyase, the enzyme that degrades S1P, had increased resistance to cisplatin, Zu-An Zhu 1 , Zheng-Qiu Zhu 2 , Hong-Xing Cai 3 , Ying Liu 4 * whereas mutants overexpressing the enzyme were more sensitive to the drug (Andrieu-Abadie and Levade, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…These prodeath functions of ceramide are mediated through direct binding to protein targets such as the tumor suppressor phosphatase PP2A (9), kinase suppressor of Ras (10), and autophagy protein LC3B-II (7). Ceramides also play an essential role in neural stem cell differentiation, mediated via direct binding to the kinase PKC (8).…”
mentioning
confidence: 99%